KINETIC STUDY OF THE REACTION BETWEEN THE CYCLOPALLADATED COMPLEX [PdCl(C2,N-dmba)(tu)] (dmba = N,N-DIMETHYLBENZYLAMINE, tu = THIOUREA) AND L-CYSTEINE - Félix, Diego B. [UNESP] (2024)
Cancer is a severe disease that causes a significant number of deaths worldwide every year. Treatments have been available, such as cisplatin, to help combat this disease. However, recent studies have shown that the enzyme system glutathione/glutathione S-transferases (GSH/GST) can cause resistance of tumor cells to this type of cancer treatment. Fortunately, there are alternatives, such as using palladium complexes such as [PdCl(C2,N-dmba)(tu)], which have demonstrated effectiveness against cancer cells. However, even these metallopharmaceuticals can be inhibited by GSH/GST system, which can modify the chemical structure of the complex and prevent it from working as an anticancer agent. That’s why it’s crucial to study the reaction between the complex [PdCl(C2,N-dmba)(tu)] and L-cysteine using techniques such as NMR, mass spectroscopy, UV-Vis spectroscopy, and stopped-flow. The study of this type of reaction will help researchers understand how these organometallics work in biological systems and how we can improve them to treat cancer more effectively.